A relação entre saúde mental e emocional no desempenho escolar em ensino de Ciências da Natureza: um estudo de caso - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The research's main theme was academic performance in Natural Sciences in High School and its relationship with students' mental and emotional health. Having as participants teenagers from the Nossa Senhora do Patrocínio State High School in the city of Dom Pedrito/RS, enrolled in regular classes, addressing the concept and characteristics of mental and emotional health according to some authors and organizations, linking them to the family, school and community development of these adolescents and how this affects their academic performance. The research presented some of the main disorders that affect this age group, in addition to the main causes that generate these aspects. The research had the general objective of analyzing the relationship between mental and emotional health and academic performance in Natural Sciences of regular high school students at a public school in the city. The research developed dealt with a qualitative approach of an exploratory nature, using a case study as a procedure and for data collection, a questionnaire with open and closed questions, a field diary and a focus group with the participation of a health professional were used. (psychologist). Description Language was used as a data analysis methodology. As main results, a survey revealed that: the majority of participants have a good family relationship, with their friends and in their romantic relationships. Students understand that their interpersonal relationships are of great importance for their development in the transition to adulthood, as well as setting goals for future plans, in addition, they regularly feel and go through strong emotions during school and these emotions often end up interfering with their school performance, which also occurs in the Teaching of Natural Sciences. However, knowing how to deal with these situations and understanding that specialized support is often necessary for your physical, mental and emotional health. It is expected that the results described in this work will contribute in general and, in particular, in the area of Natural Sciences Teaching, regarding attention to aspects related to students' mental and emotional health.
Keywords: Educação básica.; Ansiedade; Depressão; Aprendizagem; Basic education.; Anxiety; Depression; Learning; CNPQ::CIENCIAS EXATAS E DA TERRA